Fluids in the diet of people practicing mountain tourism - consumption assessment - Stawiarska, Aleksandra; Mikulec, Anna; Zborowski, Marek; Banach, Marta (Journal of Education, Health and Sport, 2023)
Proper hydration of the body and preventing dehydration is a factor that determines the preservation of health and life. The state of water and electrolyte homeostasis is necessary for the proper functioning of the human body. In conditions of increased physical activity, there is a greater exposure to the risk of dehydration, which deteriorates the functional efficiency of the body and the ability to perform physical effort, and increases the risk of thermal disorders. The aim of the study was to assess quantitatively and qualitatively the consumption of fluids among people practicing mountain hiking and to compare the obtained results with the current recommendations regarding the principles of proper hydration of the body. The research tool was a questionnaire consisting of open questions and choices regarding the method of hydration on a daily basis and in the post-exercise period. The research group consisted of 355 people aged 16 and over, including 263 women and 92 men. Daily fluid intake was usually between 1-2 l/day and 2-3 l/day. Insufficient hydration in the peri-exercise period has been observed. 39% of people start hydrating the body only during the hike, which is wrong. 61% of the respondents declare the consumption of liquids in an insufficient amount of 0.1-05 l for each hour of physical exertion, which leads to progressive dehydration. Among the surveyed people, 44% reach for caffeinated beverages in the pre-exercise period, 15% consume alcoholic beverages during this period. Introduction Forms of physical activity practiced in difficult terrain and climatic conditions in the mountains, such as: trekking, nordic walking, skyrunning, mountain biking, mountain climbing, rock climbing are demanding types of physical activity with an increased level of risk. Practicing physical activity at high altitudes above sea level and in various climatic conditions, it is extremely important, in addition to the appropriate supply of clothing and mountain equipment, to provide the body with the right amount of energy, fluids, macro and microelements according to the level of strenuous physical effort and energy expenditure. It is especially important to properly hydrate the body and prevent dehydration. A balanced balance of water and electrolytes is necessary for the proper functioning of the human body. Aim The aim of the study was to assess quantitatively and qualitatively the consumption of fluids among people practicing mountain hiking. Material and methods The study was conducted using the diagnostic survey method in January 2022 with the use of a proprietary survey questionnaire. The diagnostic survey using a questionnaire was conducted in an electronic form (on-line). The study involved 355 people aged 16 and over, including 263 women and 92 men. The questionnaire was divided into two parts: the metric and the proper part. The proper questions concerned the subject of hydration during mountain tourism, covered issues related to the habits and choices of the respondents in terms of the amount and quality of fluids supplied before, during and after the mountain hike. Questions about the type of fluids used and their knowledge of fluid needs. They were asked about recognizing the symptoms of dehydration and how to deal with dehydration. The collected results were subjected to statistical analysis. Results The vast majority of the respondents practiced mountain tourism in a recreational way, which was declared by 92% of the respondents (328 people). The surveyed people declared a varied frequency of mountain hiking. More than half of the participants set out on mountain trails several times a year, which was confirmed by 181 people. The remaining people practiced mountain tourism several times a month, which was declared by 15% (53 people), once a month by 14% (47 people), and once a year by 13% (44 people). Once a week 5% (16 people), several times a week 3% (13 people). The level of knowledge and the method of irrigation of the surveyed people, both in quantitative and qualitative terms, showed great diversity. Conclusions Among the surveyed people, 42% do not know their basic needs for fluids. On a daily basis, fluid intake is usually in the range of 1-2 l / day and 2-3 l / day. In conditions of increased physical activity, most of the surveyed people do not meet their fluid requirements and do not properly implement the strategy of pre-exercise hydration of the body. 61% of the respondents declare the consumption of liquids in the amount of 0.1-05 l for each hour of physical effort, which is below the recommended amount. Too little fluid during exercise leads to dehydration of the body. Among the surveyed people, 44% reach for drinks with caffeine in the composition in the pre-workout period. Among the surveyed people, 15% consume alcoholic beverages (mainly beer) in the period around exercise. There is a need for education in this area.